Prior vaccination prevents overactivation of innate immune responses during COVID-19 breakthrough infection - Chan, Leslie; Pinedo, Kassandra; Stabile, Mikayla A; Hamlin, Rebecca E; Pienkos, Shaun M; Ratnasiri, Kalani; Yang, Samuel; Blomkalns, Andra L; Nadeau, Kari C; Pulendran, Bali; O'Hara, Ruth; Rogers, Angela J; et al. (Science translational medicine, 2025)
At this stage in the COVID-19 pandemic, most infections are "breakthrough" infections that occur in individuals with prior severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exposure. To refine long-term vaccine strategies against emerging variants, we examined both innate and adaptive immunity in breakthrough infections. We performed single-cell transcriptomic, proteomic, and functional profiling of primary and breakthrough infections to compare immune responses from unvaccinated and vaccinated individuals during the SARS-CoV-2 Delta wave. Breakthrough infections were characterized by a less activated transcriptomic profile in monocytes and natural killer cells, with induction of pathways limiting monocyte migratory potential and natural killer cell proliferation. Furthermore, we observed a female-specific increase in transcriptomic and proteomic activation of multiple innate immune cell subsets during breakthrough infections. These insights suggest that prior SARS-CoV-2 vaccination prevents overactivation of innate immune responses during breakthrough infections with discernible sex-specific patterns and underscore the potential of harnessing vaccines in mitigating pathologic immune responses resulting from overactivation.